Amine-assisted synthesis of FeWO4 nanorodg-C3N4 for enhanced visible light-driven Z-scheme photocatalysis. (1st March 2019) - Ojha, Devi Prashad; Karki, Hem Prakash; Song, Jun Hee; Kim, Han Joo
Abstract: Highly crystalline FeWO4 nanorods (FWO NRs) were prepared using an amine in a hydrothermal reaction. A photocatalyst active to visible light was designed by preparing 5FWO/g-CN heterostructures via in-situ hydrothermal methods. Fabricated heterostructures were analyzed using X-ray diffraction (XRD), diffuse reflectance spectroscopy (DRS), BET measurements, transmission electron microscopy (TEM), X-ray photoelectron microscopy (XPS), and Fourier transform spectroscopy (FTIR). The photocatalytic activity toward the degradation of salicylic acid (SA) was investigated under visible light irradiation. The active species trapping experiments showed that the holes, as well as the electrons, exhibited an obvious influence on the photocatalytic degradation process. Examinations of the mechanism showed that the enhanced photocatalytic activity was mainly ascribed to reduced recombination rate and band gap broadening in a Z-scheme mechanism, which enhance the efficient transfer and the oxidation potential of the holes. Graphical abstract: Highlights: Wolframite-type FeWO4 nanorod was synthesized hydrothermally using triethanolamine. Photodegradation of salicylic acid was enhanced by FeWO4 /g-C3 N4 heterostructure. Predominant active species were identified by using scavengers. Z-scheme photodegradation mechanism was suggested.